Domain-specific neural substrates underlie the framing effect - Sai Sun; Jianping Hu; Rongjun Yu (NeuroImage: Reports)
Human decision-making can be influenced by whether the option is framed as positive or negative, known as the framing effect. Neuroeconomic studies have shown the engagement of the amygdala underlies the framing effect by automatically incorporating emotional (or intuitive) information into the decision process, thus leading to ''irrational'' decisions or decision biases (De Martino et al. 2006). However, these studies focus only on the gain domain in which the initial state is appetitive, leaving the mechanisms of the framing effect in the loss or aversive domain less understood, which could be equally important or even more dominant for human survival. In the present study, we first replicated De Martino et al.’s research on the framing effect in the gain domain. We then checked the commonality and distinctiveness of the framing effect across gain and loss domains using a similar experimental design combined with functional magnetic resonance imaging (fMRI). Behaviorally, participants showed comparable framing effects in both domains, suggesting a domain-general decision bias. Neuronally, the amygdala represented the framing effect for the gain domain, and its connectivity to vmPFC was positively modulated by framing bias, consistently shown in De Martino et al.’s study. Moreover, the striatum represented the framing effect for the loss domain, and its connectivity to dmPFC was subject to framing bias, suggesting distinctive neural substrates across two domains. Our study accentuates the importance of distinguishing decision processes across appetitive or aversive domains and highlights the role of the cortical-striatal-limbic network underlying the framing effect.